Competitive Advantage between Malaysia and World Halal Producers of Ruminant Meat - Yusoff, Hebat Hisham Mohd; Ismail, Normaz Wana; Sidique, Shaufique Fahmi Ahmad; Kamarulzaman, Nitty Hirawaty (Universitas Muhammadiyah Yogyakarta, 2022)
The gap created by the mismatch between high domestic demand and low domestic supply of halal meat has been filled by ruminant meat sourced from the international markets. However, the exporting countries are still limited due to stringent halal requirements. This study examined the competitive advantage of trading partners in the exportation of ruminant meat. Moreover, this study also identified factors underlying the import of ruminant meat and determined the comparative advantage of local production of ruminant meat. This study employed Vollrath indices through the utilization of relative export advantage, relative import advantage, and overall relative trade advantage. Analysis was conducted on 26 countries and 15 product codes of ruminant meat. The findings disclosed that the possession of competitive advantage did not exclusively belong to traditional sources but to other countries, particularly Pakistan and the Netherlands.